New signature for color octet pseudoscalars at the CERN LHC - Zerwekh, Alfonso R.; Dib, Claudio O.; Rosenfeld, Rogerio [UNESP] (American Physical Society (APS), 2008)
Color octet (pseudo)scalars, if they exist, will be copiously produced at the CERN Large Hadron Collider (LHC). However, their detection can become a very challenging task. In particular, if their decay into a pair of top quarks is kinematically forbidden, the main decay channel would be into two jets, with a very large background. In this brief report we explore the possibility of using anomaly-induced decays of the color octet pseudoscalars into gauge bosons to find them at the LHC. © 2008 The American Physical Society.